Application of botulinum toxin type A in gummy smile: case report - MOREIRA,David Costa (2019)
ABSTRACT Gummy smile is one of the major complaints of patients, due to its influence on the self-esteem. It is known that it has a multifactorial cause and can be present in the excessive vertical growth of the maxilla, excessive labial contraction, short upper lip and extrusion of the anterior teeth. The use of the botulinum toxin can be associated with additional treatments or be applied individually, according to the need of each patient. The goal of this research study was to present a clinical case using botulinum toxin type A as an alternative therapy to correct the gummy smile. A 22-year-old patient, presenting vertical maxillary growth, reporting aesthetic discomfort while smiling, chose for an alternative treatment therapy with the application of botulinum toxin to correct the accentuated gingival display. The results show that the toxin is a satisfactory treatment option and its indication is considered a fast, effective, easy and safe treatment method, being a more conservative approach compared to surgical procedures.